How Do We See The Non Luminous Objects? 12-13 Years Old Students’ Mental Representation of Vision - Ravanis, Konstantinos (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2018)
In this paper, we present the findings of a research which has two objectives: firstly, it recorded 12-13 years old (7th grade) students’ mental representation regarding the vision of non-luminous objects, and, secondly, it emphasized on the relative cognitive fields. The research was done through interviews of 107 urban area students in Greece. The students were asked to explain how objects become visible, stressing the following themes: The manner in which our eyes help us see the objects, whether natural or artificial light helps us see the objects and in what way, and if the objects emit light. The data analysis led to the recording of the students' basic mental representation on the one hand, while on the other hand emphasized the reemission or reflection of light by the luminous objects as a basic mental representation.From the research results, it can be concluded that through a teaching intervention based on mental representation we can foster and enhance scientific thinking and learning about light and vision.